History - Towers of Modernism : The Tendency Towards Technological Mega-projects in the 20th Century - Laak, Dirk van; Justus Liebig University Giessen (My University, 2008)
In recent history, there has never been a lack of good, impressive, and convincing ideas presented to solve the complex problems of mankind. In many cases the reality has been less successful. Even when, especiallywhen, the plan was ambitious and technical. Often massive projects had massive consequences that hadn t been considered before. Therefore, it might be advisable to take a historically informed look back at the intellectual environment in which these technologically large-scale projects were conceived. Unquestionably attractive plans, like the Solar Energy Partnership with Africa , may benefit from looking at examples from the past in order to avoid making the same mistakes in their future realisation.
Keywords: ddc:330